Optimizing the Potential of Pengulon Village Tourism Objects in Tourism Village Development Planning - Ni Made Ayu Randika Januartini; I Gusti Ayu Agung Raycitta Bulan Febrianti; Luh Meriyantin; Putu Indah Pramesti; Ni Nyoman Wiyastika Putri; I Wayan Pardi (Universitas Pendidikan Ganesha, 2026)
Pengulon Village in Gerokgak District, Buleleng Regency, Bali, has significant natural tourism potential, particularly its unique twelve-tiered waterfall that is not yet widely known. Other potential attractions include terraced rice fields, plantations, river streams, and natural springs suitable for agrotourism, ecotourism, as well as spiritual tourism and retreats. However, this development faces challenges such as limited infrastructure and accessibility, insufficient supporting facilities, low participation and capacity of local human resources, as well as inadequate promotion and effective storytelling. Additionally, overlapping authority in managing border tourism sites with Patas Village requires close coordination. Recommended development strategies include improving infrastructure, strengthening inter-village collaboration, empowering and training local communities, developing ecotourism and conservation concepts, optimizing digital promotion and storytelling, and implementing continuous monitoring and evaluation. With the implementation of these strategies, it is hoped that Pengulon Village can develop into a sustainable tourist destination, providing equitable economic and social benefits, while preserving the local environment and culture.